TELAMON: Effelsberg Monitoring of AGN Jets with Very-High-Energy Astroparticle Emissions - Kadler, M.; Bach, U.; Berge, D.; Buson, S.; Dorner, D.; Edwards, P. G.; Eppel, F.; Giroletti, M.; Gokus, A.; Hervet, O.; Heßdörfer, J.; Koyama, S.; et al. (Proceedings of Science, 2022)
We introduce the TELAMON program, which is using the Effelsberg 100-m telescope to monitor the radio spectra of active galactic nuclei (AGN) under scrutiny in astroparticle physics, namely TeV blazars and candidate neutrino-associated AGN. Thanks to its large dish aperture and sensitive instrumentation, the Effelsberg telescope can yield radio data superior over other programs in the low flux-density (Sv) regime down to several 10 mJy. This is a particular strength in the case of TeV-emitting blazars, which are often comparatively faint radio sources of the high-synchrotron peaked type. We perform high-cadence high-frequency observations every 2-4 weeks at multiple frequencies up to v = 44 GHz. This setup is well suited to trace dynamical processes in the compact parsec-scale jets of blazars related to high-energy flares or neutrino detections. Our sample currently covers about 40 sources and puts its focus on AGN with very-high-energy astroparticle emission, i.e., TeV blazars and neutrino-associated AGN. Here, we introduce the TELAMON program characteristics and present first results obtained since fall 2020.
CRIS-Team Scopus Importer:2024-12-16